Pre-service English language teachers' perceptions and motivation towards technology use in online education - Degirmencioglu, Zehra; Gilanlioglu, Ilkay (Sage Publications Ltd, 2025)
This study examined the perceptions and motivation of 64 pre-service English language teaching (ELT) teachers at an international university in North Cyprus towards technology use in online language education. It employed a mixed-methods approach. The quantitative data were analysed using SPSS 25 while the analysis of the qualitative data involved a combination of thematic analysis performed manually with the use of Leximancer 5.0 software. The findings revealed a general consensus on the benefits of technology for motivation and educational outcomes. The qualitative insights highlighted transformative themes. To illustrate, emotions such as excitement and curiosity were found to drive pre-service teachers' inclination towards technology integration. The study underscored the significance of technology in modern English language teaching and English language teacher education, offering several profound pedagogical implications.
Keywords: English language teacher education; English language teaching; motivation; online education; perceptions; pre-service English language teachers; technological tools; technology